Outcome of Interfragmentary Screw Fixation in Displaced Extra-Articular Metacarpal Fractures - Zubair Khalid, Farhan Qazi, Majid Zaheer, Hafiz Iftikhar Ahmed Sadaqat, Muhammad Umar Hafeez, Amanullah (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To report the outcome in terms of union in cases treated with interfragmentary screw fixation of displaced extra-articular metacarpal fractures. Study Design: Retrospective study. Place and Duration: The Department of Orthopedic surgery, Ghurki Trust Teaching Hospital Lahore, Pakistan from January 2021 to December 2021. Methodology: During the study period, a total of 79 cases of both genders aged 18-60 years with unilateral displaced metacarpal fractures within 2 weeks and undergoing interfragmentary screw fixation were analyzed. A special format was designed to record all study data. Information like gender, age (years), side involvement (left or right) and occupational details were noted. Patients were followed up till 16th week to label the union at the last follow up. Results: In a total of 79 cases undergoing interfragmentary screw fixation for displaced extra-articular metacarpal fractures, 49 (62.0%) were male and 30 (38.0%) female representing a male to femal ratio of 1.6:1. The mean age was noted to be 37.64±11.81 years while 51 (64.6%) cases were aged between 18-40 years. Residential status of 54 (68.4%) cases was rural. Socio-economic status of 43 (54.4%) cases was low. Right side was involved in 50 (63.3%) cases. Thirty two patients (40.5%) were manual workers. Table-1 is showing socio-demographic characteristics of all cases undergoing interfragmentary screw fixation for displace extra-articular metacarpal fractures. At the final follow up (16th week), union was reported in 75 (94.9%) cases while remaining 4 (5.1%) cases were having non-union. Practical Implications: Comparative studies are necessary to further establish the efficiency of contemporary approaches regarding treatment of extra-articular metacarpal fractures. Conclusion: Outcomes in terms of union in cases treated with interfragmentary screw fixation of displaced extra-articular metacarpal fractures were very good. Keywords: Interfragmentary screw fixation, metacarpal fracture, outcome, union.